EFEKTIVITAS SISTEM NILAI TUKAR MENGAMBANG BEBAS DALAM INFLATION TARGETING FRAMEWORK DI INDONESIA - Nini Sulaini; Wahyu Ario Pratomo (Departemen Ekonomi Pembangunan USU, 2014)
Since the economic crisis hit most of the East Asian country in 1997/1998, Indonesian government has changed its exchange rate system from managed floating system to free floating system. This has led the exchange rate of Indonesian rupiah to became more fluctuatif against other currency. Central bank needs to secure rupiah against other currency by doing intervention for the exchange rate, as we know Indonesian foreign exchange market gets unstable condition because of the crisis. This method known as fear of floating. As the application of Inflation Targeting Framework (ITF), this study using VAR model and reveals how the interest rate affect the inflation and whether inflation targeting or fear of floating method is applied within Indonesian monetary system after free floating system.Keywords : exchange rate, inflation targeting, fear of floating, VAR